No Easy Solution : A Smorgasbord of Factors Drive Remittance Costs - da Silva Filho, Tito Nicias Teixeira (IMF Working Papers; Working Paper, 2021)
There has been a global push to decrease the cost of remittances since at least 2009, which has culminated with its inclusion in the Sustainable Development Goals in 2015. Despite this effort and the emergence of new business models, remittance costs have been decreasing very slowly, disproving predictions that sharp declines would be just around the corner. In addition, remitting to poorer countries remains very expensive. Oddly, this situation has not been able to elicit academic interest on the drivers of remittance costs. This paper delved deeply into the remittances ecosystem and found a very complex, heterogenous and unequal environment, one in which costs are driven by a myriad of factors and where there are no easy and quick solutions available, which explains the disappointing outcome so far. Nonetheless, it also shows that while policymakers have limited room to act they still have a very important role to play.